Seberapa Layak Pembiayaan Perbankan Syariah di Indonesia? Sebuah Pendekatan Systematic Literature Review - Kholid Kholid (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2024)
Islamic banking financing has become a crucial component of the Indonesian financial sector, providing a sharia-compliant alternative to conventional financing. Despite its rapid growth, assessing the feasibility of Islamic banking financing remains a major challenge, particularly in terms of risk management, financial sustainability, and regulatory compliance. Previous studies have assessed the feasibility of financing using various methods, including the 5C approach (Character, Capacity, Capital, Collateral, and Condition). However, research in this area remains fragmented, with a lack of systematic analysis of key trends, methodologies, and influencing factors. This study uses a Systematic Literature Review (SLR) to synthesize and analyze existing research on the feasibility of Islamic banking financing in Indonesia. The review covers studies published between 2020 and 2022, focusing on the distribution of research, analytical techniques, and key determinants affecting the feasibility of financing. The findings reveal that most studies emphasize credit risk assessment, financial literacy, and the regulatory framework, but lack a unified approach to measuring feasibility. The results of this study provide valuable insights for Islamic financial institutions, regulators, and researchers, highlighting the need for an integrated risk assessment model, a better regulatory framework, and enhanced financial literacy initiatives to strengthen Islamic banking financing in Indonesia. This research contributes to the development of a more structured and comprehensive framework for evaluating financing feasibility, ensuring sustainable growth and financial inclusion in the Islamic banking sector.